Freemasons in the Argentinean interior: its functioning, its networks and its religious dissidence (1907-1924) - Rodríguez, Ana María Teresa (2018)
In this article we study the lodges that emerged in the first decades of the 20th century in the provinces of Argentina, specifically in the National Territory of La Pampa, a space incorporated to the Argentine State after the “Conquest to the desert” (1879). We focus on the origin and decline of four lodges: Liberty (General Acha 1907-1910), Star of La Pampa (Santa Rosa-1907-1912), Luz de La Pampa (General Pico, 1909-1914), Triangle Light of La Pampa (Catriló, 1923-1924), its functions, its networks and their connections with other civil associations. We also consider the relationship that these lodges established with the Catholic Church as they disagreed with Catholicism over the course that the territory of La Pampa should acquire.